The geochemistry and element mobility during albitization and related uranium mineralization, Rohil deposit, Rajasthan, India - Debalin Rout; Rajagopal Krishnamurthi; Ambika Prasad Kushwaha; Shailendra Kumar Sharma (Discover Geoscience)
Abstract The albitite-hosted, Mesoproterozoic Rohil uranium deposit (Latitude: 27° 33′ 25ʺ N; Longitude: 75° 29′ 25ʺ E) is located in the Sikar district, Rajasthan of Western India. The predominant radioactive mineral found is uraninite, with smaller amounts of brannerite and coffinite. Uranium mineralization is hosted by albitized metasedimentary rocks such as quartzite, quartz-biotite schist, quartz-amphibole schist, and graphite schist. These rocks have undergone multiple alteration phases, including extensive albitization. The alteration patterns can be explained by sequential metasomatic processes: Na-metasomatic stage, Na-Ca-Mg metasomatic stage, and K-metasomatic stage. Significant mobility of most major and trace elements is indicated by the mineralogical, petrographic, and geochemical evidences. The whole-rock chemistry of altered samples and unaltered host rocks has been compared to determine the extent of metasomatic alteration in the rocks of the Rohil area. Compared to the unaltered rock, the albitites of Rohil show higher Na, Si, Al, Ca, Mg, Ti, K, and P contents, while Fe and Mn are depleted. Most of the selected trace elements show significant enrichment in albitites except Th and Cs. Hf and Ta were immobile during albitization. Albitites also show an enrichment of the total REE concentration, with the LREE relatively more enriched than the HREE. Albitite samples with high U content are significantly enriched in LREE. Uranium and a few other elements were transferred and deposited by the Na-Ca-Mg-rich fluids. In albitites, U-enrichment and constant Th/U ratios of < < 1, which decreased to 0.01, suggest that U was remobilized and later deposited by metasomatic-hydrothermal activity.